Enforcement Law Against Prisoners Prisoners in the Crime of Corruption of Bribery and Gratification : Case Study at Class I Correctional Institution Medan - Ryan Perdana Simamora; Rahul Ardian Fikri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The State of Indonesia is a state of law, which means that all legal regulations in force in the State of Indonesia must be obeyed by citizens and state administrators. However, in fact, there are still many legal regulations that are violated by citizens and state administrators, such as in cases of corruption. Corruption in Indonesia is very rampant from year to year. Therefore, it is necessary to enforce the law on corruption in order to realize upholding the rule of law, upholding justice and realizing peace in society. However, it is very worrying, it turns out that the law enforcement of corruption in Indonesia is classified as very weak. This can be seen from the fact that there are still many lawmakers or law enforcers themselves who commit acts of corruption. The formulation of regulations regarding criminal acts of corruption is a long process that has been going on since the issuance of Law Number 1 of 1946 concerning Criminal Law Regulations on February 26, 1946 which made the legal basis for changing Wetboek van Strafrecht voor Netherlands Indie to Wetboek van Strafrecht (WvS), which later known as the Criminal Code. Until now, the regulations regarding criminal acts of corruption are still undergoing changes, with the latest amendments being through Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes and Law Number 7 of 2006 concerning Ratification of the United Nations Convention Against Corruption , 2003 (United Nations Convention Against Corruption, 2003). From the long journey of formulating regulations regarding criminal acts of corruption, it turns out that legal loopholes are still found, especially in the regulation regarding criminal acts of corruption, bribery and gratuities.